ROLE OF FAMILY AND ENVIRONMENT IN THE USE OF SOCIAL MEDIA AND THE IMPACT OF BULLYING BEHAVIOR IN JUNIOR HIGH SCHOOL - Raihan; Durachman, Yusuf; Sutrisna, Achmad; Siregar , Mulki; Siregar , Cahyono (International Journal of Psychosocial Rehabilitation, 2020)
Structural Equation Modeling (SEM) is a statistical modeling technique that is highly cross-sectional, linear, and complex. SEM is also a combination of two multivariate techniques that confirmatory factor analysis and path analysis. In this study, Structural Equation Modeling is applied to analyze the factors that influence the individual behavior of students at Junior High School. Where researchers take two latent variables, there are family and environment with intervening factors is the media. The data used in this study are primary data obtained using a questionnaire to students of class VII and class VIII with a total number of 181 students and have committed or been victims of bullying / Harassment. This study aims to determine the effect of family and environment on the individual behavior of junior high school students with intervening media variables. The results of this study notes that the model developed has been suitable to be used to identify and meet the criteria for the goodness of fit. From the analysis of the model, the t-value for the family latent variable is 6.35 and the t-value for the environmental latent variable is 3.91, while the intervening media variable is 6.98. With a critical value of 1.96 (for a real level of 5%) it was concluded that the latent variables of the family and the environment and the media influenced the individual behavior of a junior high school student.